Factors for the Acceptance and Use of a Learning Management System in Students of an Ecuadorian University - Ocampo-Alvarado, Juan Carlos; Ullauri-Ugarte, María Paulina (Revista Electrónica Educare, 2021)
Introduction. Despite the proven efficiency of Learning Management Systems (LMS), their success will depend on the use and acceptance of students. Therefore, it is essential to understand the relationship between the factors that determine their use in order to design effective strategies, actions, and initiatives that promote LMS usage. Objective. To analyze the factors that influence the acceptance and use of LMS in Ecuadorian university students. Method. The final sample consisted of 304 students from four different degree programs at a private university; the students filled out a questionnaire designed based on the Technological Acceptance Model derived from the theory of reasoned action. The reliability and validity of the instrument were analyzed, and then the Partial Least Squares structural equation modeling (PLS-SEM) was used. Results. The instrument showed an adequate internal consistency and a tetrafactorial structure. The results suggest that computational self-efficacy has a positive influence on ease of use and perceived utility. These, in turn, affect attitude towards use, which directly influences the use of the systems. Conclusion. The Technology Acceptance Model is suitable for studying factors regarding the use of LMS. On average, students perceive the systems to be easy to learn and use, but it represents little benefit. Given the influence of computational self-efficacy on the proposed model, we recommend taking action to increase student exposure to technological devices and encourage self-motivation by enhancing their skills in these.